Accelerated evolution of Protocadherin11X/Y: a candidate gene-pair for cerebral asymmetry and language. - Williams, N; Close, J; Giouzeli, M; Crow, T (2006)
It has been argued that cerebral asymmetry (the "torque") is the characteristic that defines the human brain and that morphological findings in psychosis are consistent with a deviation in this sex-dependent dimension of brain growth. Evidence from sex chromosome aneuploidies and an association within families between sex and handedness is consistent with the presence of a determinant of cerebral asymmetry (a possible correlate of language) on the X and the Y chromosomes. During hominid evolution a 3.5 Mb translocation occurred from the ancestral X chromosome to the Y chromosome, resulting in duplication of the Protocadherin11X gene, such that it is represented on the X and Y chromosomes in man, whereas there is a single X-linked gene in other mammals. We re-date the duplicative translocation to 6 million years ago, that is, close to the chimpanzee-hominid bifurcation. Sequence comparisons with the chimpanzee, bonobo, gorilla, and orangutan indicate that in contrast to earlier purifying selection there has been accelerated change in the Protocadherin11X ectodomain as well as the Protocadherin11Y sequence in the hominid lineage since the duplication. The evolutionary sequence of events together with the prior case for an X-Y homologous gene suggests that this gene-pair is a candidate for the evolution of hominid-specific characteristics including the sexual dimorphism of cerebral asymmetry, a putative correlate of language.